Antibacterial Activity of the Essential Oil from Betel leaf (Piper betle L.) against Streptococcus pyogenes and Staphylococcus aureus - Hernandi Sujono; Samsu Rizal; Sari Purbaya; Jasmansyah Jasmansyah (Department of Chemistry, Faculty of Sciences and Informatics, Jenderal Achmad Yani University, 2019)
Betel leaf (Piper betle L) is a medicinal plant. Its essential oil has antibacterial activity of phenolic compounds and theirs derivatives that can inhibit a wide range of bacteria. Streptococcus pyogenes and Staphylococcus aureus is a bacteria that can cause strep throat (pharyngitis). This study was conducted to determine how to obtain the essential oil of Betel leaf green (Piper betle L.) using steam-water distillation method and determine the antibacterial activity of essential oils of betel leaf (Piper betle L.) against the bacteria Streptococcus pyogenes and Staphylococcus aureus using wells method. Betel leaf 5 kg isolated using steam-water distillation of essential oils produces as much as 9 mL, yield of 0.135%, a specific gravity of 0.750 g / mL, and the refractive index of 1.337. The results of GC-MS analysis of betel leaf green essential oil obtained 10 Most compounds are compounds chavicol, eugenol, germacrene D, caryophyllen, eugenol acetate, 2-allyphenol, β-chamigrene, α-cadinene, terpineol, and α-humulene. Based on the test results of the antibacterial activity of betel leaf that the essential oil of betel leaf green (Piper betle L) at the concentration of 10%, 20%, 30%, and 40% can inhibit the bacteria Streptococcus pyogenes and Staphylococcus aureus, the category of barriers weak to moderate for bacteria Streptococcus pyogenes and weak to strong resistance categories for Staphylococcus aureus bacteria.